CHRISTOLOGY AND PLURALISM OF RELIGIONS AN ASIAN PERSPECTIVE - Sinaga, Rotua Dominika (Kariwari: Jurnal Pendidikan Agama Katolik dan Pastoral, 2024)
The task of the laity is to "direct the world to Christ." This does not mean forming a Christian society, but creating the possibility of believing in Christ, allowing the attitude of faith from the human side. Faith is not a spontaneous natural reaction, it is not an instinct that occurs automatically and is forced, nor is it an action taken because it is forced, but is free and autonomous. In this situation, in all the reviews described here, the service and role of lay people are placed.